A comparative study of caudal anesthesia with bupivacaine v/s bupivacaine with dexmedetomidine in lower abdominal surgeries in pediatric age group - Kumar N., Kishore; Kadam, Sandeep (Pain medicine, 2021)
Background: caudal anaesthesia has shortterm effect. Alpha2 adenoreceptors when used as adjuvant to local anaesthetic in children prolongs analgesic duration. The study is aimed to assess the efficacy of addition of dexmedetomidine with Bupivacaine in caudal block for extending postoperative analgesia and its safety profile in pediatric infraumbilical surgeries. Method: the prospective interventional longitudinal double blinded study was conducted on 60 patients randomly divided into two groups by simple lottery method: group B who received (0.25 %) bupivacaine 1 ml/kg plus 1 ml normal saline (NS), and those in group BD who received (0.25 %) bupivacaine 1 ml/kg plus 0.5 μg/kg dexmedetomidine in 1 ml NS. Postsurgery, both groups were compared in R studio v1.2.5001. Association between the adverse effect and other variables (age, gender, type of surgery, groups) were assessed by Multiple linear regression. Results: in group BD, duration of analgesia prolonged significantly (P < 0.05). In group BD, FLACC score at initial four hours and at 12th hour was significantly less (P < 0.05). Group B was more likely to receive high number of rescue analgesia (P = 0.0005; OR = 11.769). No significant difference was observed concerning hemodynamics, respiratory parameters and adverse effect between both groups (P > 0.05). Conclusion: in children, dexmedetomidine when used along with bupivacaine prolongs postoperative analgesia duration, without any significant side effects.